Parametric Studies on Triangular Tension Leg Platform - Hamzah, Abdul Hazeem (2010)
Tension Leg Platform (TLP) is a buoyant platform held in place by mooring system. TLP's are similar to conventional fixed platforms except that the platform is maintained on location through the use of moorings held in tension by the buoyancy of the hull. The cost for TLP increases with the water depth. More studies are going on to find solution to reduce the cost on TLP design. This study focuses on the influence of energy spectrum model on the triangular TLP. Pierson-Moskowitz (PM) and JONSWAP spectrum were used in this study. Wave forces were estimated at the instantaneous position of the platform by Morison's equation with Airy's linear wave theory. Wave is considered to act unidirectional in the surge direction only. All forces acting on the platform were calculated to determine the TLP's response in surge, heave and pitch degrees of freedom. Lab test had been done to support and justify the motion response calculated in the numerical calculation. As a conclusion. only a small significant difference in surge. heave and pitch motion response distance for both PM and JONSWAII energy spectrums. but the frequencies of the TLP motion on surge. heave and pitch degree of freedom can effects the TLP tethers.